Complement-dependent cytotoxicity of human autoantibodies against myelin oligodendrocyte glycoprotein - Kohyama, Kuniko; Nishida, Hiroya; Kaneko, Kimihiko; Misu, Tatsuro; Nakashima, Ichiro; Sakuma, Hiroshi (Frontiers in Neuroscience, 2023)
Background The autoantibody to myelin oligodendrocyte glycoprotein (MOG), a component of the central nervous system myelin, has been identified in a subset of demyelinating diseases. However, there is no convincing evidence to support the direct pathogenic contribution of this autoantibody. Objective To elucidate the role of anti-MOG autoantibodies in human demyelinating disorders, we assessed the effect of autoantibodies on MOG-expressing cells. Methods Mammalian cells expressing the human MOG protein reacted with human anti-MOG autoantibodies in the presence or absence of complement. Sera from 86 patients and 11 healthy sera were used. We analyzed anti-MOG antibody titers, IgG subclass, and their cytotoxic ability in sera from patients with various neurological diseases. Membrane attack complex (MAC) formation was examined by detection of complement C9 or C9neo with western blot or flow cytometry. Results Among 86 patients, 40 were determined to be MOG-IgG-positive and 46 were negative. Anti-MOG-positive sera, but not -negative sera, caused cell death in MOG-expressing cells. This cytotoxic effect was disappeared after heat inactivation of sera. Importantly, anti-MOG IgG and externally added complement were necessary for sufficient cytotoxic effects. Anti-MOG autoantibodies were histologically colocalized with complement and formed a membrane attack complex consisting of anti-MOG IgG and complement factors. Conclusion The human MOG antibody specifically killed MOG-expressing cells in vitro in the presence of externally added complement. Membrane attack complexes were formed on the cells, indicating that this autoantibody activated complement-mediated cytotoxicity. Further studies in larger numbers of patients are needed to characterize the role of complement in MOGAD.